Maternal supplementation with balanced fatty acid fat powder enhances sow reproductive performance and offspring intestinal health by modulating mitochondrial fusion and cell apoptosis - Xiao, Kan; Zhang, Yanbing; Zhang, Minfang; Liu, Jiahao; Guo, Junjie; Zhao, Shiwei; Xu, Xiao; Chen, Shaokui; Liu, Yulan (Frontiers in Nutrition, 2025)
IntroductionFatty acids play a critical role in meeting energy demands and maintaining intestinal health of pigs. Maternal dietary fatty acid composition may influence offspring growth and intestinal integrity. This study aimed to investigate the effects of supplementing sow diet with a balanced fatty acid fat powder (BFAFP) during late gestation and lactation on reproductive performance and offspring intestinal health, and to explore the underlying regulatory mechanisms.MethodsIn Exp. 1, a total of 24 multiparous sows (d 90 of gestation) were divided into two groups including a control diet (U:S ratio: 5.08; n-6/n-3 PUFA ratio: 7.72) supplemented with 2% soybean oil and an experimental diet containing 2% BFAFP (U:S ratio: 2.98; n-6/n-3 PUFA ratio: 3.13) which was composed of fish oil, flaxseed oil, red palm oil, coconut oil, soybean oil, and lysophospholipids. At farrowing, sow blood and colostrum were collected. In Exp. 2, at d 21 of lactation, twenty-four suckling piglets were chosen and used in a 2 × 2 factorial arrangement and the main factors including diet (maternal supplementation of soybean oil or BFAFP) and lipopolysaccharide (LPS) challenge (saline or 100 μg/kg BW LPS injection). At 4 h post LPS injection, suckling pigs were killed for intestinal tissue sample collection.ResultsCompared with soybean oil, maternal supplementation with BFAFP not only significantly enhanced the number of weaned piglets, weaning survival rate, and milk yield (P < 0.05), but also showed trends for increasing total litter weight at weaning (P = 0.073), total litter weight gain (P = 0.058), and individual piglet daily gain (P = 0.074). Maternal BFAFP supplementation increased the concentrations of lactose, protein and non-fat solids as well as IgA and IgM concentrations in colostrum (P < 0.05). Moreover, maternal BFAFP supplementation significantly increased jejunal villus height post-LPS challenge in piglets (P < 0.05). Maternal BFAFP supplementation also reduced jejunal mRNA expression of tumor necrosis factor α, and interleukin-1 β and mitigated LPS-induced downregulation of claudin-1 mRNA (P < 0.05). Moreover, Maternal BFAFP supplementation upregulated jejunal mRNA and protein expression of mitofusin-1 and mitofusin-2 after LPS challenge (P < 0.05). Finally, maternal BFAFP suppressed jejunal mRNA expression of caspase-3 and caspase-9 in piglets after LPS challenge (P < 0.05).DiscussionMaternal BFAFP supplementation enhanced sow reproductive performance and offspring growth while protecting offspring against LPS-induced intestinal damage, likely through promoting mitochondrial fusion and attenuating inflammatory response and cell apoptosis.